Selective serotonin reuptake inhibitors to improve outcome in acute ischemic stroke: possible mechanisms and clinical evidence. Issue 10 (23rd September 2015) - Siepmann, Timo; Penzlin, Ana Isabel; Kepplinger, Jessica; Illigens, Ben Min‐Woo; Weidner, Kerstin; Reichmann, Heinz; Barlinn, Kristian
Abstract Background Several clinical studies have indicated that selective serotonin reuptake inhibitors (SSRIs) administered in patients after acute ischemic stroke can improve clinical recovery independently of depression. Due to small sample sizes and heterogeneous study designs interpretability was limited in these studies. The mechanisms of action whereby SSRI might improve recovery from acute ischemic stroke are not fully elucidated. Methods We searched MEDLINE using the PubMed interface to identify evidence of SSRI mediated improvement of recovery from acute ischemic stroke and reviewed the literature on the potential underlying mechanisms of action. Results Among identified clinical studies, a well‐designed randomized, double‐blind, and placebo‐controlled study (FLAME ‐ fluoxetine for motor recovery after acute ischemic stroke) demonstrated improved recovery of motor function in stroke patients receiving fluoxetine. The positive effects of SSRIs on stroke recovery were further supported by a meta‐analysis of 52 trials in a total of 4060 participants published by the Cochrane collaboration. Based on animal models, the mechanisms whereby SSRIs might ameliorate functional and structural ischemic‐brain damage were suggested to include stimulation of neurogenesis with migration of newly generated cells toward ischemic‐brain regions, anti‐inflammatory neuroprotection, improved regulation of cerebral blood flow, and modulation of the adrenergic neurohormonal system. However, to date, it remains speculative if and to what degree these mechanisms convert into humans and randomized controlled trials in large populations of stroke patients comparing different SSRIs are still lacking. Conclusion In addition to the need of comprehensive‐clinical evidence, further elucidation of the beneficial mechanisms whereby SSRIs may improve structural and functional recovery from ischemic‐brain damage is needed to form a basis for translation into clinical practice.